Does overreaction exist for contrarian strategies in the Nepalese stock market? - Malla, Raja Ram; Basnet, Dinesh (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: The study aims to investigate the existence of the short-term overreaction effect in the Nepalese stock market and to assess whether short-term contrarian strategies can generate abnormal profits for investors.Design/methodology/approach: Using monthly stock return data from NEPSE spanning July 2014 to July 2019, this study applies the cumulative average return method and three regression models across sixteen short-term buy and hold horizons to investigate both the existence of overreaction effects and the profitability of contrarian investment strategies.Findings: The empirical results indicate no significant evidence of short-term overreaction effects in the Nepalese stock market. Further, none of the short-term contrarian strategies yielded significant results to yield abnormal returns during the studied period.Conclusion: Findings indicate no evidence of short-term overreaction in NEPSE, suggesting relative market efficiency and the ineffectiveness of contrarian strategies for generating excess returns.Implications: These results emphasize that investors should be wary of contrarian strategies in Nepal’s market and that policymakers must strengthen settlement and liquidity frameworks to ensure any fleeting inefficiencies are neither masked nor unexploitable.Originality/value: This study contributes to the limited literature on overreaction under behavioural finance in emerging markets, particularly in the context of the underexplored Nepalese stock market.JEL Classification: G14, G41, G11, G15